The role of leverage in mediating the effect of profitability on company value (Case study of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2013-2023) - Rahma, Shifa Meisyah; Mahmudi, Bambang (ARKA INSTITUTE, 2025)
One important indicator in assessing a company's prospects is its value as reflected in its share price, which is generally influenced by profitability and leverage. In this study, company value is measured using Price to Book Value (PBV), profitability is proxied by Return on Assets (ROA), and leverage is measured through Debt to Equity Ratio (DER) as an intervening variable to assess the mediating role of leverage on the relationship between profitability and company value in food and beverage sub-sector issuers on the IDX. This quantitative study involved all companies in the sub-sector during the period 2013–2023, using purposive sampling, which produced 77 samples. The results show that ROA has a significant positive effect on PBV (t-count 4.651 > t-table 2.012; sig 0.000 < 0.05), while DER has no positive effect on PBV (t-count 1.572 < t-table 2.012). ROA was also found to have a negative effect on DER (tcount -2.785 > ttable 2.011). The Sobel test confirmed that DER did not act as a mediating variable (sig 0.171 > 0.05). Thus, ROA and DER can affect company value, but only the relationship between ROA and PBV and ROA and DER were found to be significant.